2008
DOI: 10.1093/pasj/60.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Observations of 6.7GHz Methanol Masers with the Japanese VLBI Network

Abstract: We have observed 13 methanol maser sources associated with massive star-forming regions: W 3(OH), Mon R2, S 255, W 33A, IRAS 18151 $-$ 1208, G 24.78 $+$ 0.08, G 29.95 $-$ 0.02, IRAS 18556 $+$ 0136, W 48, OH 43.8 $-$ 0.1, ON 1, Cep A, and NGC 7538 at 6.7GHz using the Japanese VLBI Network (JVN). Twelve of the thirteen sources were detected at our longest baseline of $\sim$ 50M $\lambda$ , and their images are presented. Seven of them are the first VLBI images at 6.7GHz. The high detection rate and the small fri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 66 publications
13
32
0
Order By: Relevance
“…The emission is constrained to the velocity interval −1.5 km s −1 and −4.5 km s −1 . The morphology and velocity field that we find of the 6.7 GHz methanol masers agree well with previous measurements using different telescopes: Vlemmings et al (2010) (MERLIN); Sugiyama et al (2007Sugiyama et al ( , 2008b (VERA). One notable difference between our spectrum and earlier measurements is the lack of a feature at ∼ −4.6 km s −1 as seen by both Vlemmings et al (2010) and Sugiyama et al (2008a).…”
Section: 7 Ghz Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The emission is constrained to the velocity interval −1.5 km s −1 and −4.5 km s −1 . The morphology and velocity field that we find of the 6.7 GHz methanol masers agree well with previous measurements using different telescopes: Vlemmings et al (2010) (MERLIN); Sugiyama et al (2007Sugiyama et al ( , 2008b (VERA). One notable difference between our spectrum and earlier measurements is the lack of a feature at ∼ −4.6 km s −1 as seen by both Vlemmings et al (2010) and Sugiyama et al (2008a).…”
Section: 7 Ghz Resultssupporting
confidence: 91%
“…Recent multi-epoch observations of water masers in the region indicate the presence of a slower wide-angle outflow in addition to the high-velocity collimated jet observed in radio continuum (Torrelles et al 2010). Sugiyama et al (2008b) find the 6.7 GHz methanol maser emission to be constrained to two individual clumps with blueshifted masers to the east and redshifted masers in a linear configuration to the west. Moreover, single-dish monitoring of the 6.7 GHz methanol masers has shown the variation in the maser emission in the blueshifted and redshifted cluster to be synchronised and anti-correlated (Sugiyama et al 2008a).…”
Section: Introductionmentioning
confidence: 84%
“…Kinematics of the maser spots revealed that outflow/infall dominates over the possible Keplerian rotation in a disc. A similar morphology with a similar kinematic signature was found in the well-known HMSFR Cep A, where, due to additional constraints on the orientation, the radial motions are more likely resulting from infall (Torstensson et al 2011a, Sugiyama et al 2008. Moreover, it seems that the magnetic field plays a role in shaping this morphology (Vlemmings et al 2010).…”
Section: The Morphology Of 67 Ghz Maserssupporting
confidence: 71%
“…1c). There are some morphological differences to the southeast of the elongated 3 The 6.7 GHz CH 3 OH maser observations carried out with the Japanese VLBI Network (JVN; Sugiyama et al 2008) and the European VLBI Neatwork (EVN; Surcis et al 2012) were performed without phase-referencing and it is thus impossible to establish the absolute position of the masers. However, the CH 3 OH maser distribution seems to match the OH maser distribution (Brebner et al 1987;Hutawarakorn & Cohen 1999); since the latter are associated with cores A and B, it seems likely that the methanol masers are also associated with these two cores.…”
Section: Continuum Emissionmentioning
confidence: 99%